New insights for the use of quercetin analogs in cancer treatment. (November 2017) - Iacopetta, Domenico; Grande, Fedora; Caruso, Anna; Mordocco, Roberta Alessandra; Plutino, Maria Rosaria; Scrivano, Luca; Ceramella, Jessica; Muià, Noemi; Saturnino, Carmela; Puoci, Francesco; Rosano, Camillo; Sinicropi, Maria Stefania
Aim: Quercetin (Q1 ) is a flavonoid widely present in plants and endowed with several pharmacological properties mostly due to its antioxidant potential.Q1 shows anticancer activity and could be useful in cancer prevention. On the other hand, Q1 is poorly soluble in water and unstable in physiological systems, and its bioavailability is very low.Methods: A small set ofQ1 derivatives (Q2–Q9 ) has been synthesized following opportunely modified chemical procedures previously reported. Anticancer activity has been evaluated by MTT assay. Human Topoisomerases inhibition has been performed by direct enzymatic assays. Apoptosis has been evaluated by TUNEL assay. ROS production and scavenging activity have been determined by immunofluorescence.Results: The anticancer profile of a small library ofQ1 analogues, in which the OH groups were all or partially replaced with hydrophobic functional groups, has been evaluated. Two of the studied compounds demonstrated an interesting cytotoxic profile in two breast cancer models showing the capability to inhibit human Topoisomerases.Conclusion: The studied compounds represent suitable leads for the development of innovative anticancer drugs.